2018
DOI: 10.3390/sports6030094
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Asymmetries in Ultrasound Assessments of the Rectus Femoris throughout an NCAA Division I Volleyball Preseason

Abstract: The purpose of the study was to assess glycogen content of the rectus femoris (RF) muscles utilizing high-frequency ultrasound throughout an intensive, nine-day preseason training period in NCAA division I volleyball athletes. In the morning prior to the beginning of practice, athletes (n = 13) left and right RF muscles were assessed via ultrasound to quantify muscle fuel ratings (0–100 score range). The recommended location of the RF ultrasound scans were based on manufacturer guidelines, and the same technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Two studies used sessional-RPE (e.g., value of perceived session difficulty obtained by multiplying the duration of the session by the RPE) 95 to track internal load (perceived effort) of sport practices, training sessions, or games alongside measures of biomechanical asymmetry or performance measures. 62,67 Unfortunately, neither of these studies attempted to examine the statistical relationship of RPE with lower limb biomechanics and asymmetry. The remaining three studies tracked introspective state measures including RPE and perceived muscle soreness 47,49,79 at multiple timepoints in a training season to monitor changes across time.…”
Section: Rate Of Perceived Exertion and Biomechanical Asymmetriesmentioning
confidence: 99%
“…Two studies used sessional-RPE (e.g., value of perceived session difficulty obtained by multiplying the duration of the session by the RPE) 95 to track internal load (perceived effort) of sport practices, training sessions, or games alongside measures of biomechanical asymmetry or performance measures. 62,67 Unfortunately, neither of these studies attempted to examine the statistical relationship of RPE with lower limb biomechanics and asymmetry. The remaining three studies tracked introspective state measures including RPE and perceived muscle soreness 47,49,79 at multiple timepoints in a training season to monitor changes across time.…”
Section: Rate Of Perceived Exertion and Biomechanical Asymmetriesmentioning
confidence: 99%
“…The final publication involved the use of MuscleSound ® to monitor resting levels of glycogen in U.S. Division 1 collegiate female volleyball players on each morning of a 9 day pre-season training camp [ 35 ]. The MuscleSound ® information was provided in the form of muscle fuel rating, which, as previously noted, remains unvalidated in a peer-reviewed published format.…”
Section: The Literature Involving Musclesound ® Assessment Of Muscle Glycogenmentioning
confidence: 99%
“…Although endurance-trained muscle is known to have higher resting glycogen stores than non-trained muscle (e.g., 500 vs. 350 mmol/kg dw [ 36 ]), it is difficult to imagine that the magnitude of difference between legs within the same well-trained athlete would be as large as reported, albeit with a different assessment metric (muscle fuel rating of 52 vs. 33 points). The authors suggested that bilateral asymmetries in glycogen content in volleyball athletes might be used to assess for injury risk, noting that large asymmetries and bilateral deficits in muscle strength are sometimes linked to injuries in athletes [ 35 ]. Although this would be a potentially valuable application, there is presently no validation of either the muscle fuel rating score as a measure of muscle glycogen, whether glycogen utilisation patterns are sufficiently different between limbs across a range of symmetrical and asymmetrical exercise activities detected by any technique, nor whether this is associated with injury risk or patterns.…”
Section: The Literature Involving Musclesound ® Assessment Of Muscle Glycogenmentioning
confidence: 99%
“…The adaptation of a user-friendly perioperative nutrition screen and non-invasive point-of-care muscle health diagnostic tools may better identify this unrecognized predictor of poor outcome. 4,32 In the opinion of these authors, effective and essential ways to advance anesthesiology within health systems and within the health care ecosystem are through greater clinical involvement, inquiry, and greater scholarly investment in perioperative medicine to secure our professional future over the next decade and beyond. To quote our colleague and friend from the University of Southamptom, Professor Mike Grocott, "Perioperative medicine is the future of anesthesia, if our specialty is to thrive."…”
Section: Clinical Pathwaysmentioning
confidence: 99%